A new tool for failure analysis in small firms: frontiers of financial ratios based on percentile differences (PDFR). Issue 4 (2nd October 2018) - Tascón, María T.; Castaño, Francisco J.; Castro, Paula
ABSTRACT: This paper proposes an innovative methodology based on the use of differences between percentiles to compute the scores and distances to failure of a specific firm or group of firms. This approach is based on significant differences between the group of failed firms and the population to which the failed firms belong (meaning the same industry, period and geographical zone selected) and eliminates the effects of correlation between the factors selected to compute the scores. The use of accounting ratios, which can be computed using data available in the mandatory financial statements, and the homogenisation of these variables using percentiles make percentile difference frontier of ratios a tool specially oriented to small and medium-sized enterprises (SMEs). Our results for the selection of the most discriminant variables are consistent with those of previous studies, and the hit rates of failed and non-failed firms outperform those of the commonly used traditional methodologies. In addition, the proposed methodology enables us to compute distances to failure of both individual firms and groups of firms. Finally, this methodology identifies which of the financial drivers used are strengths or weaknesses for the specific firm or group of firms under study for purposes of a potential reorganisation.